A SIX-PORT MEASUREMENT DEVICE FOR HIGH POWER MICROWAVE VECTOR NETWORK ANALYSIS - KOMMEY, Benjamin; ADDO, Ernest Ofosu; TAMAKLOE, Elvis; TCHAO, Eric Tutu; NUNOO-MENSAH, Henry (Applied Computer Science, 2022)
The changes experienced in technology due to the third industrial revolution have over the years contributed immensely to the development of efficient devices and systems. As a result, solutions have been provided to challenges encountered in the heating industry. However, higher efficiency and better performance has undoubtedly been highly sort after. This paper presents the complete industrial development of a new system of a microwave device for use in S-band networks (2.45 GHz ISM band in this application): a vector network analyzer (VNA). The VNA, which is designed based on the six-port measurement principle, provides accurate measurements of both magnitude and phase of the load reflection coefficient. The device is designed to have high power handling capabilities and works under the full operating conditions of high-power microwave generators. Initial measurements show that the device perform stable and can perform temperature-independent measurements over protracted periods. The system is suited for on-line monitoring and control of network parameters in industrial waveguide applications..